2005
DOI: 10.1007/s10384-004-0147-y
|View full text |Cite
|
Sign up to set email alerts
|

A Review of 244 Orbital Tumors in Japanese Patients During a 21-Year Period: Origins and Locations

Abstract: The pathologic profiles of orbital tumors were characterized according to patient age and the location of the tumor in the orbit. The age of onset, tumor location, and radiological findings provide us with important information for the diagnosis of a tumor prior to biopsy or tumor resection and for the determination of the treatment strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
82
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 8 publications
15
82
1
4
Order By: Relevance
“…2,5,9 The frequency and distribution of tumor diagnosis and their association with age is in accordance with past studies that too have demonstrated a relatively higher frequency of vascular and lacrimal gland tumors among operable orbital neoplasms. 3,5,[9][10][11][12][13] Proptosis is the commonest presentation reported in orbital tumors, and in our series the mean proptosis is quite similar to previous data. 3,14,15 In effect, our series is a universally representative sample of orbital tumors.…”
Section: Discussionsupporting
confidence: 90%
“…2,5,9 The frequency and distribution of tumor diagnosis and their association with age is in accordance with past studies that too have demonstrated a relatively higher frequency of vascular and lacrimal gland tumors among operable orbital neoplasms. 3,5,[9][10][11][12][13] Proptosis is the commonest presentation reported in orbital tumors, and in our series the mean proptosis is quite similar to previous data. 3,14,15 In effect, our series is a universally representative sample of orbital tumors.…”
Section: Discussionsupporting
confidence: 90%
“…It accounts for 0.01 % of all lymphomas but for 5% to 10% of all orbital tumors. 1,2 The clinical manifestations are non-specific. Radiological diagnoses are only seen in various case reports.…”
Section: Introductionmentioning
confidence: 99%
“…Two third of the benign tumors and one third malignant tumors occur in the orbit [1]. The orbital tumor has low incidence of diagnosis and there are several complications after treatment or operation such as cosmetic problems, severe ophthalmological deficit with loss of vision and eye movement [2]. It is most important to obtain maximum information about the orbital tumor prior to deciding the appropriate treatment strategy in the order to manage post-operative complications [3][4][5].…”
Section: Introductionmentioning
confidence: 99%